Biliary Adenofibroma of the Liver: Report of a Case and Review of the Literature - Gurrera, Alessandra (SAGE-Hindawi Access to Research, 2010)
We herein report the clinicopathologic features of a rare case of biliary adenofibroma (BAF) of the liver in a 79-year-old man. Grossly, tumour presented as a well-circumscribed, 5.5-cm mass with a solid and microcystic appearance. Histological examination was typical of biliary adenofibroma, showing a proliferation of variable-sized tubulocystic structures embedded in a moderately cellular fibrous stroma. Immunohistochemistry, revealing immunoreactivity of the epithelial component to cytokeratins 7 and 19, was consistent with a bile duct origin. Notably, the stromal cells had a myofibroblastic profile, showing a diffuse and strong expression of vimentin and α-smooth muscle actin. Differential diagnosis with Von Meyenburg complex, biliary adenoma, biliary cistadenoma, congenital biliary cystsy, and hepatic benign cystic mesothelioma is provided. The occasionally reported expression of p53 in biliary adenofibroma has suggested that this tumour could represent a premalignant lesion. The absence of both cytological atypia and p53 immunoreactivity in our case confirms that BAF is a benign tumour with an indolent clinical behaviour. However, a careful histological examination of BAF is mandatory because malignant transformation of the epithelial component has been documented in two cases.